Pemberitaan Pemain Naturalisasi Dalam Media dengan Analisis DNA Dan Visone - Barus Angumboro Putra Wakhid (Commsphere: Jurnal Mahasiswa Ilmu Komunikasi, 2024)
Sports mass media have recently been discussing the discourse on the naturalization of national team players. This discourse is a project initiated by PSSI (All Indonesia Football Association) and BTN (National Team Agency). The reason for doing this is to boost the national team's performance to achieve more in the international arena. This naturalization discourse has raised pros and cons in the eyes of national football lovers. This naturalization issue has been linked to media interest in reporting it. From this problem, the author has a question: how do the media in Indonesia frame the news of the Naturalization of Indonesian National Team Players in recent times? The study used qualitative research and media framing analysis techniques. Data collection was carried out by observation and observation of several media. As for the data analysis technique, this study used media framing analysis with the DNA and Visone applications to determine the media's bias in its reporting. The existence of these similarities makes a country's sovereignty that must be loved. Several specific media reports naturalized players with certain frames to lead readers to be pro or con. This study concluded that some media in Indonesia framed the news of naturalization positively because the increasing achievements of the national team can prove it. A small portion of the media viewed it negatively because it was difficult for local players to defend the Indonesian national team. Keywords: Naturalized player, Framing analysis, DNA and Visone